The Working of the Pre-War Gold Standard - Walker, C. H. (Review of Economic Studies, 1934)
Journal Article The Working of the Pre-War Gold Standard Get access Charles H. Walker Charles H. Walker London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 1, Issue 3, June 1934, Pages 196–209, https://doi.org/10.2307/2967483 Published: 01 June 1934